Bank Syariah Indonesia Gold Pawn Law in Denpasar, Bali - I Kadek Semara Atmika; Wilma Silalahi (International Journal Labs, 2023)
This study aims to analyze the legal contract for Sharia gold pawn financing in an Islamic bank in Denpasar and explain the suitability of theory and practice that occurred in the field after the issuance of the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN MUI) Number 26/DSN-MUI/III/2002 regarding Gold Rahn which was conveyed by the bank in the inauguration of the BSI Gold Pawn Halal Agreement. This study uses a qualitative descriptive-analytical research method in which the primary source is based on direct fieldwork by observing the phenomena that occur and processes in real terms, then analyzing the suitability between theory and practice in depth. This research shows that gold pawning at the Denpasar Indonesian Islamic Bank uses 3 contracts, namely qardh, rahn, and ijarah contracts. The implementation of gold mortgage financing is not fully by Sharia, because it is indicated that the usury in giving ujrah is taken according to the amount received by the customer. In the ijarah ujrah contract, it must be calculated from the estimated value, so that there is a discrepancy between theory and practice that occurs in the field. This documents the context of content analysis which is different from the DSN MUI fatwa No. 26/DSN-MUI/III/2002 concerning Gold Rahn, because, in a qardh contract, there is no addition to profit.